Patrick R. Michaud wrote:
none(none($a,$b),none($c,$d)) == none($a,$b,$c,$d)
True.
Hmmmm...
-> none(none($a,$b) == none($a,$b,$c,$d), none($c,$d) == none($a,$b,$c,$d))
RHS distributes first. So the expansion is this instead...
-> none(none(none($a,$b),none($c,$d)) == $a, none(none($a,$b),none($c,$d)) == $b, none(none($a,$b),none($c,$d)) == $c, none(none($a,$b),none($c,$d)) == $d, )
-> none(none(none($a,$b)=$a, none($c,$d)=$a), none(none($a,$b)=$b, none($c,$d)=$b), none(none($a,$b)=$c, none($c,$d)=$c), none(none($a,$b)=$d, none($c,$d)=$d), )
-> none(none(0, 1), none(0, 1), none(1, 0), none(1, 0), )
-> none(0, 0, 0, 0, )
-> true
Ummm, what am I missing? To state it another way... we can
show that none($a,$b) == none($a, $b, $c, $d) is true,
RHS distributes first again:
none($a,$b) == none($a, $b, $c, $d)
-> none( none($a,$b)==$a, none($a,$b)==$b, none($a,$b)==$c, none($a,$b)==$d, )
-> none( 0, 0, 1, 1, )
-> false
Damian